PRELIMINARY DISCUSSIONS ON ISSUES RELATED TO A EUROPEAN BUSINESS CODE - Dan VELICU (Challenges of the Knowledge Society)
The standardisation of European law occurred in rapid steps in the last decades. However, there is no code or uniform regulation of commercial relations that occur between subjects with an address or seat on the territory of the European Union. Such a regulation could significantly increase the process of economic integration and the dynamics of commercial exchanges. There are several initiatives, but the development of a European business code represents a titanic task. In addition, any approach in this sense requires putting on the table the real needs, obstacles and possible and alternative solutions. Without claiming to be exhaustive, the present study aims to start a serious research with practical effects in order to identify the problems of such an approach and to find effective solutions in the face of real impediments.